2019
DOI: 10.1007/978-3-319-96415-7_2
|View full text |Cite
|
Sign up to set email alerts
|

Sub-voxel Perfusion Modeling in Terms of Coupled 3d-1d Problem

Abstract: We study perfusion by a multiscale model coupling diffusion in the tissue and diffusion along the one-dimensional segments representing the vasculature. We propose a block-diagonal preconditioner for the model equations and demonstrate its robustness by numerical experiments. We compare our model to a macroscale model by [P. Tofts, Modelling in DCE MRI, 2012].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Motivated by the observation in [29], that in a discrete finite element setting the trace operator is stable as a map L 2 (Ω) → L 2 (∂Ω), we propose an alternative approach to construct the preconditioners. We start off by outlining the construction of an operator ∂ n, : H 1 (Ω p ) → L 2 (Γ) which will be an approximation to ∂ n .…”
Section: Approximating the Trace Normal Gradient Operatormentioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by the observation in [29], that in a discrete finite element setting the trace operator is stable as a map L 2 (Ω) → L 2 (∂Ω), we propose an alternative approach to construct the preconditioners. We start off by outlining the construction of an operator ∂ n, : H 1 (Ω p ) → L 2 (Γ) which will be an approximation to ∂ n .…”
Section: Approximating the Trace Normal Gradient Operatormentioning
confidence: 99%
“…We remark that when using the finite element method, the identity or the mass matrix has eigenvalues such that both the smallest and the largest eigenvalues scale as h d on uniform mesh. First we consider S = I, with eigenvalues ≈ h. Then, following [29], we let S = h −1 I, i.e., a matrix with eigenvalues ≈ 1. Finally, the choice of S = (−∆ + I) −1/2 is included to show that the relevant trace space in (12) is not (by viewing the trace as an order 1/2 operator) H 1/2 so that dual variable would reside in H −1/2 .…”
Section: Approximating the Trace Normal Gradient Operatormentioning
confidence: 99%
“…Related models have been used to study the proliferation of cancer drugs, [27][28][29] the transport of oxygen, [30][31][32][33][34] and nanoparticle transport for hypothermia therapy. 35 A recent study 36 describes contrast agent perfusion based on diffusive transport with a mixed-dimension model. The herein presented fluid-mechanical model is similar to the drug proliferation model described in Cattaneo and Zunino 27,37 and introduced in Possenti et al 28 It is derived here for the specific application of contrast agent perfusion in brain tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Different strategies have been proposed to remedy this, e.g., Kuchta et al studied suitable preconditioners in [27]. Holter et al then applied this preconditioner to simulate flow through the microcirculature found in a mouse brain [23]. An alternative coupling scheme was intro-duced by Köppl et al in [25], where the source term was taken to live on the boundary of the inclusions.…”
Section: Introductionmentioning
confidence: 99%